The Development of Ict-Based Mathematics Instructional Media On Linear Program Subject For Students of Grade XI SMA/MA - Khalida, Puji Karunia (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research is constructed based on the lack of instructional media that capable of deliver the information and learning materials of Linear Program. Developing the computer-based instructional media will help students understanding the learning materials easier. This research and development using the model designed by Borg and Gall modified by Sugiyono. This research aimed to improve ICT-based mathematics instructional media which is qualifying the validity and practically to help students in grade XI SMA/MA in order to understanding Linear Program materials. Subjects for this research are 33 students of XI SMA Negeri 1 Pekanbaru. This research is using three types of validation questionnaire, consists of material, media, and students response. The questionnaire was analyzed both in quantitative and qualitative ways. Based on the results of small-group data analysis and discussion can be concluded that ICT-based instructional media is valid and sufficient for practicality with an average value of 0.979.